The Book of Kings and exilic identity: 1 and 2 Kings as a work of political historiography - Lovell, Nathan (The Library of Hebrew Bible/Old Testament Studies, 2021)
Cover -- Title -- Copyright -- Contents -- List of Figures and Tables -- List of Abbreviations -- Preface -- Chapter 1 Kings as Political Historiography -- 1.1. Introduction -- 1.2. Method and Previous Work -- 1.3. Challenges to Reading Kings as Political Historiography -- 1.3.1. The Literary Context of Kings and DtrH -- 1.3.2. The Historical Context of Kings -- 1.3.3. Summary and Synopsis of the Present Work -- Chapter 2 The Narrative Strategy of Kings -- 2.1. The Challenge of Structuring Kings -- 2.2. Juxtaposition and Meaning: The Aborted Attack on Moab -- 2.3. The Literary Structure of Kings -- 2.3.1. Narrative Arcs in Kings: The Word of God and Its Fulfilment -- 2.3.2. Kings as Narrative Intercalation -- 2.3.3. The Plot: Inner and Outer Kings -- 2.3.4. Supporting Evidence -- 2.4. Conclusions: The Narrative Strategy of Kings -- Chapter 3 Covenant: What Is Israel? -- 3.1. The Mosaic Covenant in Kings -- 3.2. The Covenant as Destiny: A Framework for Political Identity -- 3.2.1. Deuteronomy and Political Identity -- 3.2.2. David within the Covenant -- 3.2.3. The Covenant and Repentance: Josiah's Reforms -- 3.2.4. Covenant, Grace, and Destiny -- 3.3. The Covenant within the Historiography of Kings: Political Redefinition -- 3.3.1. Conquest: Solomon's Golden Age -- 3.3.2. Conflict: Elijah's Struggle for the Soul of Israel -- 3.3.3. Crisis: The Assyrian Dark Ages -- 3.3.4. Why the Exile? Manasseh as Culmination -- 3.4. Conclusions -- Chapter 4 Nationhood: Who Is Israel? -- 4.1. Nationhood: The Name 'Israel' -- 4.1.1. The United Monarchy -- 4.1.2. Judah -- 4.1.3. Both Peoples, but Neither Kingdom -- 4.2. Israelite Boundary Markers and the Nations: The Resettlement of 2 Kings 17 -- 4.3. Israel-Incipient: The Preservation of a Remnant -- 4.3.1. The Ahab Cycle: From Baal to Jeroboam's Yahwism -- 4.3.2. The Jeroboam Cycle: From Israel to Judah.